Guest Editorial. (16th January 2023) - Hackney, Fiona; Rana, Mah; Gant, Nick; Hill, Katie
This introduction to 'Well-Making and Making-Well: Craft, Design and Everyday Creativity for Health and Well-Being' outlines some of the background, thinking and research that underpins well-making as a concept and approach. Entangled in everyday lived experiences of health and creativity, well-making is concerned with the changes that can happen when people make things together, paying attention to the processes, places, people and materials involved. Well-making is applied and engaged research which, more often than not, involves working collaboratively with stakeholder partners and community groups. The editors of this Special Issue argue that, while well-making is a concept/approach in process, the articles here and related research help us better understand the principles that underpin this work, enabling more productive outcomes when we make together and helping to evidence the beneficial impact of such research.